Hypoxia and angiogenesis: regulation of hypoxia-inducible factors via novel binding factors - Chen, Li (Korean Society of Medical Biochemistry and Molecular Biology, 2009)
The mechanisms that regulate angiogenesis in hypoxia or hypoxic microenvironment are modulated by several pro- and antiangiogenic factors. Hypoxia-inducible factors (HIFs) have been established as the basic and major inducers of angiogenesis, but understanding the role of interacting proteins is becoming increasingly important to elucidate the angiogenic processes of a hypoxic response. In particular, with regard to wound healing and the novel therapies for vascular disorders such as ischemic brain and heart attack, it is essential to gain insights in the formation and regulation of HIF transcriptional machineries related to angiogenesis. Further, identification of alternative ways of inhibiting tumor growth by disrupting the growth-triggering mechanisms of increasing vascular supply via angiogenesis depends on the knowledge of how tumor cells develop their own vasculature. Here, we review our findings on the interactions of basic HIFs, HIF-1α and HIF-2α, with their regulatory binding proteins, histone deacetylase 7 (HDAC7) and translation initiation factor 6 (Int6), respectively. The present results and discussion revealed new regulatory interactions of HIF-related mechanisms.